An Evidence Practice Gap in Antiemetic Prescription with Chemotherapy - Chepsy C-Philip; Biju George (Research Center for Rational Use of Drugs (RCRUD), 2015)
Background: Chemotherapy induced nausea and vomiting is an added distress to patients burdened by the illness. In an effort to tackle the emetogenic potential of the agents, guidelines have been proposed to maintain uniformity in prescription and improvement in patient tolerance; but their utility and practice is not consistent. The aim of this clinical audit was to assess the antiemetic.practice and investigate the adherence to antiemetic clinical practice guideline Methods: We performed an audit of the antiemetic practices in our tertiary referral centre. A.questionnaire based interview was completed at the outpatient visit to tabulate the data Results: 99 (81.8%) patients received chemotherapy of at least low emetogenic risk. 83 (84%) patients received prophylaxis which was appropriate in 65% based on the our centre's antiemetic regimen. This was however inappropriate in 76% of patients based on the international practice.parameters Conclusions: Guidelines are not uniformly representative of all populations and modifications toguidelines based on local data are required to ensure success of such policies. There exist evidence-.practice gaps in antiemetic policies